Traditional African religions in South African law - Bennett, T. W. (University of Cape Town Press, 2011)
Since colonial times, traditional African religions have been misunderstood and misrepresented. Victims of the prejudice of Christian dogma, they have been said to be nothing more than magic and superstition, or at best mere ancestor worship. South Africa’s new constitutional order, however, with its celebration of diversity and its guarantee of equal treatment, demands a change in thinking. Traditional African Religions in South African Law is a collection of essays which explores indigenous African beliefs in the South African legal system. Its comprehensive coverage includes issues of witchcraft, animal sacrifice, the African Initiated Churches, environmental protection and traditional healing and medicines. It further considers ubuntu as an underlying ethic, the freedoms of religion and culture and the distinction between them. By bringing together the perspectives of law and religious studies, this book challenges current perceptions and underscores the complexities of South Africa’s modern multicultural society.
free
Keywords: Africa; Indigenous Religions/Folk Religions/Traditional Religions; Law